Study of hair dye poisoning and its outcome in tertiary care rural institute - Rawat, Ramakant; Kumar, Manoj; Singh, Prem Shankar; Kumar, Granth; Verma, Vijay (International Journal of Research in Medical Sciences, 2017)
Background: Hair dye poisoning is not rare but is an emerging poisoning in India. The main component of hair dye causing toxicity is para phenylene diamine (PPD). Due to its easy availability and low cost, it is becoming a common mode of self-poisoning in rural area. A prospective study was planned to assess the clinical profile and outcome in patients with hair dye poisoning. Methods: This prospective observational study was conducted on 260 patients of para-phenylene-diamine (hair dye) poisoning, hospitalized in the medical unit of UP Rural Institute of Medical Science and Research, Saifai from January 2011-2014 over a period of 4 years. The diagnosis of PPD poisoning was based on history of ingestion and clinical manifestations. All cases were thoroughly evaluated for different complications and were treated accordingly. Results: Out of 260 cases enrolled, majority were females and were in the age group of 21-30 years. The intent of poisoning was suicidal in 100% cases. Cervico-facial edema was the most common presentation followed by respiratory distress, hypotension and generalised bodyache. Nephro-toxicity was observed in 58.46% cases. Myocarditis was observed in 11.53% cases. Mortality in PPD poisoning was high (21.53%) due to cardiotoxicity and renal failure Conclusions: Hair dye (PPD) poisoning is hepato-nephro as well as myo and cardiotoxic.